The Effectiveness of Antibiotic-Coated Ventriculoperitoneal Shunts for Prevention of Shunt Infections in Patients with Myelomeningocele - Ertugrul, Bilal; Kaplan, Metin; Hergunsel, Omer Batu; Akgun, Bekir; Ozturk, Sait; Erol, Fatih Serhat (Karger, 2021)
Purpose: Hydrocephalus is a common comorbidity among the newborns, with myelomeningocele (MMC) and ventriculoperitoneal (VP) shunts being frequently used for the treatment of such patients. In this study, we aimed to compare the effectiveness of antibiotic-free and antibiotic-coated shunts to reduce the rate of shunt infection in patients with hydrocephalus and accompanying MMC. Methods: 116 patients with hydrocephalus and MMC who were treated with VP shunts were included in the study. Shunt infection rates among antibiotic-free and antibiotic-coated shunts were compared. Results: Of the 116 patients included in the study, 39 had antibiotic-coated shunts and 77 had antibiotic-free shunts. Shunt infection developed in 4 of the 39 cases treated with antibiotic-coated shunts and in 5 of the 77 cases treated with shunts without antibiotics. No significant statistical difference was found between antibiotic-coated and antibiotic-free VP shunts in terms of shunt infection (p = 0.450, p > 0.05). Conclusion: In patients with MMC, using VP shunts containing antibiotics was found not to have a protective effect in preventing shunt infection. Whether the sac is intact or ruptured does not affect this result. (C) 2021 S. Karger AG, Basel
Keywords: Hydrocephalus; Infection; Meningomyelocele; Ventriculoperitoneal shunt